Analisa Jaringan Sosial dalam Menelusuri Budaya Menyimpang di Lembaga Pemasyarakatan - A. Josias Simon Runturambi (Universitas Budi Luhur, 2017)
This paper descibring problem and culture deviance inside the correctional institution. It is difficult to point out at one cause only. Social network analysis is fundamental in exploring imprisonment within correctional institution. Formal and informal social network occurs depending on reciprocity and proximity principals in the context of surviving in correctional institution. Social life within correctional institution nowadays is considered as social dinamic arena, not traditional punishment institution